Credit supply, house prices, and financial stability. (27th January 2021) - Min, Feng; Wen, Fenghua; Xu, Jiayu; Wu, Nan
Abstract: We investigate how both traditional bank credit and shadow banking credit affect housing prices and financial stress based on China's monthly data from January 2003 to December 2019. Our results show that: (a) the effects of bank credit shocks and shadow banking credit shocks on housing prices partly offset each other; (b) increasing bank loans in recessions will increase financial instability, while increasing shadow bank credit in recessions will lower financial instability; (c) commercial bank credit plays a more important role in explaining housing price fluctuations, while shadow banking credit plays a more important role in explaining financial stress fluctuations. Our results are robust to a wide battery of checks and have important policy implications.